A Pilot Study to Examine Maturation of Body Temperature Control in Preterm Infants. Issue 5 (4th September 2013) - Knobel, Robin B.; Levy, Janet; Katz, Laurence; Guenther, Bob; Holditch‐Davis, Diane
ABSTRACT: Objective: To test instrumentation and develop analytic models to use in a larger study to examine developmental trajectories of body temperature and peripheral perfusion from birth in extremely low‐birth‐weight (EBLW) infants. Design: A case study design. Setting: The study took place in a Level 4 neonatal intensive care unit (NICU) in North Carolina. Participants: Four ELBW infants, fewer than 29 weeks gestational age at birth. Methods: Physiologic data were measured every minute for the first 5 days of life: peripheral perfusion using perfusion index by Masimo and body temperature using thermistors. Body temperature was also measured using infrared thermal imaging. Stimulation and care events were recorded over the first 5 days using video which was coded with Noldus Observer software. Novel analytical models using the state space approach to time‐series analysis were developed to explore maturation of neural control over central and peripheral body temperature. Results/Conclusion: Results from this pilot study confirmed the feasibility of using multiple instruments to measure temperature and perfusion in ELBW infants. This approach added rich data to our case study design and set a clinical context with which to interpret longitudinal physiological data.